Pendampingan Manajemen Produksi untuk Meningkatkan Produktivitas UMKM Keripik Pisang Celsy Lia di Bandar Lampung - Fenty Ariani; Asep Trisna Setiawan; Maulidiana M; Robby Yuli Endra; Arnof dwi ferdiza (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting economic growth, yet they still face numerous challenges in managing their production processes. Celsy Lia Banana Chips MSME in Bandar Lampung is a processed food business with growth potential, yet it still faces several challenges, including the use of primitive production equipment, resulting in limited production capacity, suboptimal production management, and manual work processes. This community service activity aims to increase business productivity through production management assistance for partner MSMEs. The implementation method includes field observation, problem identification, production process management assistance, education related to work efficiency, and assistance in organizing a more effective production flow. The activity results show an increase in partners' understanding of the importance of structured production management, increased production process effectiveness, and a gradual increase in business production capacity. Direct assistance also helps partners identify production obstacles and determine solutions appropriate to business conditions. With this activity, MSMEs are expected to be able to increase business productivity and develop more efficient and sustainable production processes